Safety Index of Fatigue Failure for Ship Structure Details - Mao, Wengang; Rychlik, Igor; Storhaug, Gaute (2010)
One way to assess the uncertainty in fatigue damage analysis is to use a so-called safety index. In the computation of such an index, the variation coefficient for the accumulated damage is required. In this paper the expected fatigue damage and its coefficient of variation are firstly estimated from measured stress. Secondly, when suitable stress measurements are not available these are computed from models for damage accumulation and sea states variability. Stresses during the ship sailing period are regarded as the nonstationary, slowly changing, Gaussian processes, and hence damage accumulation, during encountered sea state, can be approximated by an algebraic function of significant wave height, ship speed, and heading angle. Further, the space time variability of significant wave height is modeled as a log normal field with parameters estimated from the satellite measurements. The proposed methods to estimate uncertainties in the damage accumulation process are validated using full-scale measurements carried out for a container vessel operating in the North Atlantic.